OA01.38. Anti-obesity activity of Zizyphyus mauritiana lam: a potent pancreatic lipase inhibitor - Deshpande, M. S. (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: To study anti-obesity activity of Ziziphus mauritiana Lam bark powder (ZMBP) on High Fat Diet (HFD) induced obesity in rats. METHOD: Obesity was induced in Wistar rats by feeding high fat diet (HFD) for 70 days. The obese rats were distributed in 4 groups (n=5). Group 1: Normal (lean) Control, Group 2: Obese Control, Group 3: Obese rats administered orally 250 mg/kg ZMBP daily, Group 4: Obese rats dosed with 500 mg/kg ZMBP daily, Group 5: Obese rats dosed with Standard Drug Sibutramine, 0.90 mg/kg. The rats were dosed orally daily for a period of 90 days. The animals were screened for induction of obesity by analysing obesity parameters such as Body weight, Anthropological Parameters, Serum Tryglycerides, Serum Cholesterol, Glucose tolerance test, Insulin resistance Test, DEXA analysis and MRI Scan. RESULT: At the end of 90 days treatment with ZMBP the obese rats showed 16.33 % reduction in body weight gain at 250 mg/kg and 17.38 % (P<0.05) reduction in body weight gain at 500 mg/kg when compared with the obese control group respectively. The standard drug Sibutramine showed 5.52% reduction in body weight gain when compared with the obese control group. The DEXA analysis at the end of 90 days of treatment showed 68.99 % (P<0.01) decrease in the Fat mass at 250 mg/kg dose and 72.84 % (P<0.001) decrease in the Fat mass at 500 mg/kg dose when compared with the obese control group. The pancreatic lipase activity in 250mg/kg (5.13+0.71 U/mg of protein) and in 500 mg/kg (4.01+0.86 I/mg of protein) reduced significantly (P<0.001) when compared with the obese control group (9.73+2.39 U/mg of protein) CONCLUSION: The ZMBP has anti-obesity activity at 250 mg/kg and 500-mg/kg dose. It has lipase inhibitory activity.